The Supervision of Planning and Design in Creating a New Image for a School Building as Part of a City Corridor - Caesarina, Hanny Maria; Aina, Noor (Comment: an International Journal of Community Development, 2018)
Abstract There are so many buildings that became the point of interest of a space and create a unique character for a city. Therefore, a great planning and design of the building and the environment can contribute a good image for a city. This community service activity aims to give a supervision about building and environment design of a school building that might affect image of the city. Participants were the teachers of Madrasah Ibtidaiyah Muhammadiyah (MIM) Kertak Hanyar. The tools and materials used in the supervision are a mini portable projector, laptop and Microsoft power point software. The outcomes of this activity was a new planning and design for the school that based on the character of Banjarmasin mixed with modern elements with minimum budget for the renovation. The unique character of the school roof is the element that conserved together with the specific material for the building.